Accepting Others for Peace from an Islamic Perspective: A Theological-Historical Analysis - Machasin, Machasin (Ulumuna, 2024)
This article attempts to answer the question regarding the possibility of building peace in an Islamic perspective, which is known for various teachings and practices that are contrary to peace, such as the teaching of waging holy war against the infidels and that Islam is triumphant and no other religion may defeat it. Some writers say it is impossible to speak of peace from Islamic teachings. For them, Islam is a religion of violence and not compatible whatsoever with the discourse of peace. However, it is not difficult to find in Islam materials of teaching by which one may develop concepts about peace, peacemaking, and peacebuilding. Islam itself means getting into peace and that Islam teaches justice, enjoins people to goodness, and prevents evil. Loving rather than hating is very much endorsed in Islam's ethical teaching; accepting others as they are is one way to love them. Peace not only exists but will continue forever; it must be constructed and maintained continuously.